1986
DOI: 10.1111/j.1432-1033.1986.tb09882.x
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative effect of thyroid and glucocorticoid hormones on the induction of hepatic phosphoenolpyruvate carboxykinase in vivo and in cultured hepatocytes

Abstract: The present study investigates the effect and interaction of glucocorticoid and thyroid hormones on the induction of phosphoenolpyruvate carboxykinase (PEPck) mRNA and enzyme protein under in vivo conditions and in serum-free cultured hepatocytes from hypothyroid rats.In hypothyroid/adrenalectomized rats T3 significantly enhanced the cAMP induced PEPck mRNA activity within 3 -6 h. This effect was further enhanced by the presence of glucocorticoids. The half-life of PEPck mKNA, as determined after administratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1

Year Published

1988
1988
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 26 publications
2
20
1
Order By: Relevance
“…several of these studies, T3 was seen to potentiate the effect of cAMP in inducing PEPCK mRNA levels (12,13,24). In our study, we observed no effect of T3 on expression of a transiently transfected PEPCK-CAT fusion gene containing 2,100 bp of the PEPCK promoter sequence (Fig.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…several of these studies, T3 was seen to potentiate the effect of cAMP in inducing PEPCK mRNA levels (12,13,24). In our study, we observed no effect of T3 on expression of a transiently transfected PEPCK-CAT fusion gene containing 2,100 bp of the PEPCK promoter sequence (Fig.…”
Section: Discussionsupporting
confidence: 51%
“…2A). Alternatively, as has been previously suggested (12,13), T3 may potentiate cAMP responsiveness which is mediated by a cAMP response element located close to the PEPCK gene transcription start site (31,33).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…One such mechanism might involve regulation by corticosteroids. Dexamethasone has been shown to increase cytosolic PEPCK activity and mRNA in vivo and in vitro (30)(31)(32), although this is controversial (25). Because the HH fetal lamb may be a stressed animal, it is possible that the induction of cytosolic PEPCK in these animals is in part due to an increase in corticosteroid secretion.…”
Section: Resultsmentioning
confidence: 99%
“…However, in fasted conscious dogs, there was a non-significant decrease in GNG during a 3 h portal-venous infusion of insulin [17]. Insulin influences hepatic GNG by powerfully regulating the transcription of important gluconeogenic enzymes [18,19], but the effect of enzyme expression on glucose production may not be immediate, since the mRNA half-life of many gluconeogenic enzymes is close to 1 h [20] and the enzyme itself takes several hours to degrade [21]. On the other hand, the supply of gluconeogenic substrates to the liver has an immediate impact on glucose homoeostasis by increasing GNG [22] and decreasing GLY [23].…”
Section: Introductionmentioning
confidence: 99%